IDENTIFIKASI FAKTOR LINGKUNGAN SEBAGAI DETERMINAN DIARE PADA BALITA : LITERATUR REVIEW - Kamrin, Kamrin (NHM PRESS, 2022)
Diarrhea is a disease that often occurs in children under five, both in the world and in Indonesia. WHO recorded cases of diarrhea in infants for 2013 as many as 1.5 billion cases with a mortality rate of around 760,000 cases. Meanwhile, according to UNICEF and WHO data in the same year, the death rate from diarrhea is around 2000 children under five every year. The purpose of this study was to identify environmental conditions as a determinant of diarrhea in children under five. This study uses a qualitative approach based on articles related to the determinants of diarrhea in toddlers. The sample in this study were toddlers and the respondents were mothers of toddlers. The results of this study indicate that maternal education is a determinant of diarrhea in toddlers by 18.1%, family latrines by 24.3 - 58.3%, drinking water sources by 19.8% and clean water management by 22.5% - 78, 9%. Conclusion: Determinants of diarrhea in toddlers include mother's education, family latrines, drinking water sources and clean water management.